2016
DOI: 10.1038/srep24921
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced NFκB enhanceosome requires TonEBP/NFAT5 without DNA binding

Abstract: NFκB is a central mediator of inflammation. Present inhibitors of NFκB are mostly based on inhibition of essential machinery such as proteasome and protein kinases, or activation of nuclear receptors; as such, they are of limited therapeutic use due to severe toxicity. Here we report an LPS-induced NFκB enhanceosome in which TonEBP is required for the recruitment of p300. Increased expression of TonEBP enhances the NFκB activity and reduced TonEBP expression lowers it. Recombinant TonEBP molecules incapable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
87
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 44 publications
5
87
0
Order By: Relevance
“…Originally described to be transcriptionally regulated by NFAT5 in renal epithelial cells upon hypertonic stimulation (22), COX2 expression in mechanoactivated cells is thought to be controlled by the transcription factor NF-kB (54). Interestingly, recent reports suggest that NFAT5 is capable of forming an enhanceosome with NF-kB, which is required to recruit p300 (55). Although the microarray data did not implicate that genetic ablation of Nfat5 significantly affects expression of gene sets associated with NF-kB signaling, an influence of NFAT5 on the activity and target specificity of NF-kB in the context of hypertension cannot be fully excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Originally described to be transcriptionally regulated by NFAT5 in renal epithelial cells upon hypertonic stimulation (22), COX2 expression in mechanoactivated cells is thought to be controlled by the transcription factor NF-kB (54). Interestingly, recent reports suggest that NFAT5 is capable of forming an enhanceosome with NF-kB, which is required to recruit p300 (55). Although the microarray data did not implicate that genetic ablation of Nfat5 significantly affects expression of gene sets associated with NF-kB signaling, an influence of NFAT5 on the activity and target specificity of NF-kB in the context of hypertension cannot be fully excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of TonEBP immunoprecipitation with p65 showed TonEBP Regulates Pro-inflammatory Genes DECEMBER 23, 2016 • VOLUME 291 • NUMBER 52 that cross-talk does not involve physical interaction. Interestingly, in other cells, these proteins have been shown to interact at the immediate onset of hypertonic stimulation (26) and in response to LPS treatment (28). Interestingly, NF-B activity was required for hypertonic induction of only a subset of the studied targets; TauT and CCL2 were refractory to inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the POMC promoter was also activated by a mutant TonEBP (TonEBP-DIPT) that is unable to form a homodimer and thus cannot bind and act through TonEBP response elements [25]. Moreover, the POMC promoter was also activated by a mutant TonEBP (TonEBP-DIPT) that is unable to form a homodimer and thus cannot bind and act through TonEBP response elements [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in peripheral inflammatory conditions have reported that TonEBP is critical to the recruitment of an acetyltransferase p300 to p65 subunit of NF-jB, which results in assembly of NF-jB enhancesome and leads to p300 action on opening/remodeling of chromatin and binding of proximal factors such as Sp1 and RNA polymerase II [25,31]. Our results revealed that TonEBP haploinsufficiency resulted in half the levels of TNF-a-induced COX2, IL-1b, and IL-6 as compared to the levels observed in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%